Pengaruh KerapatanBongkah Dan Jeluk Muka Air Tanah Terhadap Pertumbuhan Dan Serapan Fosfor Sawi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
groundwater levels of peat soil on growth and uptake of P in chinesse cabbage. Peat soil sample was taken from Kalampangan, Palangkaraya, Central Kalimantan in the depth of 0 - 30 em. A completely randomized factorial design was used to perform the experiment with two factors and three replicants. The fist factor was bulk density wich for levels, i.e. 0.2 g.cm'), 0.25 g.cm'), 0.30 g.cm') and 0.35 g.cm'). The second factor was groundwater level with three levels, i.e. 15 em, 30 em and 45 em. The parameters were total root length, plant heigth, fresh and dry weight of root and shoot, concentration and uptake of P in chinesse cabbage and this data are analysed by Duncan's Multiple Range Test at 5 % of significant level. The experiment showed that increase bulk density affected decrease of plant growth. Bulk density application at 0.20 g.cm') showed optimal growth of plant, and application at 0.35 g.cm') decrease plant growth. Bulk density levels has not effect on uptake Pin plant, but its increase the P concentration in plant. The all of groundwater levels application has not affected for plant growth, P concentration and uptake in chinesse cabbage.